Drivers of cryptocurrency regulation: cross-country empirical evidence from US congress data - Feridun, Mete (Routledge Journals, Taylor & Francis Ltd, 2025)
This article undertakes a cross-country empirical analysis of the cryptocurrency regulations from around the world based on a data set drawn from the November 2021 Update of the United States Law Library of Congress report on the regulation of cryptocurrencies around the world. Based on the cross-country information provided in the report, a binary variable was constructed to reflect cryptocurrency regulations in the form of an application of tax legislation and/or anti-money laundering and counter-terrorist financing (AML/CFT) laws at the jurisdiction level. Results of cross-country logit regressions show that cryptocurrency regulation is significantly and positively associated with perceptions of corruption and bribery and significantly and negatively associated with AML/CFT framework and price stability policy.
Keywords: Cryptocurrency; financial regulation; crypto assets; logistic regression